Features of the expression of melatonin MT1 receptors in the general cover of rats caused by light deprivation - Sobolevskaya, I. S.; Krasnobaeva, M. I.; Myadelets, O. D. (Морфологія / Morphologia / Morfologìâ, 2021)
Background. It has now been established that any change in the synchronized work of the circadian clock leads to a disruption of the body's regulatory systems, which consists in the development of metabolic disorders and tissue damage. Objective: to study the dynamics of the expression of the MT1 melatonin receptor in the skin of white male rats under light deprivation. Methods. In this work, using immunohistochemistry, the features of the expression of receptors for melatonin (MT1) were studied. The experiments were performed on outbred male rats weighing 170-220 g, which were divided into 2 groups; intact - animals kept under standard fixed lighting conditions (12 h light / 12 h dark); Group 2 - animals with simulated light deprivation in conditions of round-the-clock darkness (24 hours of darkness). Results. A strong circadian dependence of the expression of MT1 melatonin receptors in the general integument was established. In the cells of the epidermis and sebaceous glands, by the 14th day, MT1 expression significantly decreased, which then sharply increased by the 21st day. In the keratinocytes of the epidermis, a wavelike character of changes in indicators is noted throughout the study: an increase (7th day) - a decrease (14th day) - a sharp increase (21st day). Conclusion. Initially, light deprivation leads to a decrease in the number of immunopositive cells, and then their level increases compensatory, which is one of the manifestations of the body's adaptation mechanisms to chronodestruction.